2013
DOI: 10.1155/2013/824781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Asthma Phenotypes and Therapeutic Responses

Abstract: Asthma is a heterogeneous disease that means not all asthmatics respond to the same treatment. We hypothesize an approach to characterize asthma phenotypes based on symptomatology (shortness of breath (SOB), cough, and wheezy phenotypes) in correlation with airway inflammatory biomarkers and FEV1. We aimed to detect whether those clinical phenotypes have an impact on the response to asthma medications. Two hundred three asthmatic children were allocated randomly to receive either montelukast (5 mg at bed time)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
1
12
0
2
Order By: Relevance
“…This result is in accordance with that of Zedan et al (2013) who found that asthma symptom was insignificantly related to the age and gender of asthmatic children, with that of Ungar et al (2011) who found that asthma were more predominant in boys especially those younger than 10 years old, and with that of Pradel et al ( 2001) who found that older children have less severe asthma symptom and better control than younger children, and Petsios et al (2013) who also found that asthma was more severe in boys than girls. In contrast to two other in which they found that girls have more severe asthma symptom then the boys (Van De Ven, Engels, Sawyer, Otten, & Van Den Eijnden, 2007;Nordlund, Konradsen, Pedroletti, Kull, & Hedlin, 2011) ).…”
Section: Resultssupporting
confidence: 90%
“…This result is in accordance with that of Zedan et al (2013) who found that asthma symptom was insignificantly related to the age and gender of asthmatic children, with that of Ungar et al (2011) who found that asthma were more predominant in boys especially those younger than 10 years old, and with that of Pradel et al ( 2001) who found that older children have less severe asthma symptom and better control than younger children, and Petsios et al (2013) who also found that asthma was more severe in boys than girls. In contrast to two other in which they found that girls have more severe asthma symptom then the boys (Van De Ven, Engels, Sawyer, Otten, & Van Den Eijnden, 2007;Nordlund, Konradsen, Pedroletti, Kull, & Hedlin, 2011) ).…”
Section: Resultssupporting
confidence: 90%
“…Zedan et al reported that the shortness of breath (SOB) group of asthma patients showed significant increase in total serum IgE when compared with both the cough and the wheezy groups [24]. Since asthma and COPD shared some pathological characteristics [25], we speculated that elevated serum T-IgE might promote the airway inflammation and remodeling, and then resulted in more serious symptoms and worse status of lung function.…”
Section: Discussionmentioning
confidence: 88%
“…We did not analyze the difference in long-term drug therapy, particularly inhaled corticosteroids in these patients. Medication use and compliance of the patients may affect symptoms and lung function, although it is possible to have a similar effect on level of serum IgE [24]. Finally, the time interval between an exacerbation and the enrollment of the patients to our study needs to be mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously hypothesized an approach to classify asthma phenotypes based on validated symptomatology [shortness of breath (SOB), cough, wheezy phenotypes] in correlation with cytokine profile and airway inflammatory biomarkers aiming to detect their impact on asthma treatment [5]. Our study described a wide variability in the baseline characteristics of the proposed clinical phenotypes in which the SOB phenotype group were found to have significant increase of total sIgE, soluble interleukin-2 receptor serum concentration and decrease in FEV1 in comparison to both cough and wheezy groups.…”
Section: Editorialmentioning
confidence: 99%